PARENTS' PERSPECTIVES ON VACCINATION RUBELLA MEASLES/MR IN CHILDREN - Deni, Yuthia; Hadi, Ella Nurlaella (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background:The global measles cases increased by 79% in the first two months of 2022 compared to the same period in 2021, leading to an outbreak, including in Indonesia. In 2022, Indonesia reported a total of 4845 confirmed laboratory cases of measles and six deaths in 32 out of 38 provinces. Challenges related to parental trust and doubts about vaccines have raised the risk of outbreaks due to unvaccinated children.Purpose:To synthesize and critically assess parental perspectives and attitudes towards the use of Measles Rubella/MR vaccination in childrenMethods:The research method employed was a systematic literature review, conducted by using primary studies from PubMed, Proquest, and ScienceDirect with the keywords “Parent; MR Vaccine; Parental perspective or parent's decision; child” published between 2018-2023, in English, open access, and relevant to the topicResults:A total of 17,759 research articles were screened for eligibility, and 9 articles met the inclusion criteria. Based on the 9 reviewed articles, parental perspective of Measles Rubella/MR vaccination was influenced by six factors: vaccine, social, knowledge, disease, trust, and practicality.Conclusion:It is crucial to develop strategies that target vaccine trust and address sources of vaccine hesitancy. Maintaining a trusting partnership between parents, healthcare providers, and the government is essential in dispelling doubts about the benefits and safety of vaccines.